Abrahamyan’s Approach to Pronouns - Abajyan, Anna (Bulletin of Yerevan University B: Philology, 2025)
While re-analysing the pronouns of Modern Armenian in a new way, S. Abrahamyan classified and categorized them. According to the scholar, the classification of pronouns should be based on how the object or quality is expressed within them and what kind of relationship they indicate. Based on this principle, the Armenologist introduced modifications to the system of Modern Armenian pronouns by merging certain types and renaming others. As a result, he differentiated six types of pronouns: personal (subject), demonstrative, reciprocal, definite (general), indefinite (partial), and interrogative-relative (absolutely indefinite). He revised the definitions of personal and demonstrative pronouns and unified the definite and negative categories. He identified the morphological and syntactic features of pronouns and, as an entirely new contribution to the Armenian grammar, examined their structure, word-formation significance, and stylistic usages.
Keywords: pronoun; demonstrative; reciprocal; relative; pronominal declension; word formation; affix; compound pronoun; syntactic function; stylistic usage